Development and Performance Evaluation of a Novel Disc-Buckle Steel Scaffold Joint - Si Wei; Yu Xu; Bing Yuan; Haofan Chen; Genquan Zhong; Guoyan Zhang (Buildings, 2025)
The disc-buckle scaffold system demonstrates significant advantages in prefabricated construction applications, particularly in terms of installation efficiency, load-bearing capacity, and standardization. Guangzhou Construction Group Co., Ltd., a leading enterprise in promoting prefabricated building development in Guangdong Province, China, has collaborated with the Guangdong University of Technology to develop an innovative disc-buckle scaffold system. The main difference between different scaffolds lies in the connection part of the joint. The mechanical behavior of scaffold joint plays a critical role in determining the structural integrity of the entire scaffolding system. So, the novel disc-buckle scaffold proposed in this paper is mainly new in the joint. Finite element simulation based on the test results is employed to study the performance of the novel scaffold joint in this paper. The results show that the newly developed scaffold joint exhibits superior mechanical performance, characterized by a bending stiffness of 34.5 kN·m/rad. The joint demonstrates maximum tensile and compressive bearing capacities of approximately 108 kN and 70 kN in the transverse direction, respectively. Furthermore, the joint’s maximum shear bearing capacity exceeds 180 kN, surpassing the buckling critical force of the vertical steel pipe and satisfying all strength requirements. The scaffold joint exhibits robust hysteresis characteristics, and the wedge-shaped connection mechanism maintains consistent stiffness and load-bearing symmetry under both positive and negative bending moments. The proposed disc-buckle steel scaffold joint features a minimal number of components, achieving an optimal balance between structural performance and economic efficiency.